Phenotypic and genetic parameters of age at first calving, first lactation milk yield and some measures of efficiency of production in Murrah buffaloes - DUTT, TRIVENI; TANEJA, V K (The Indian Journal of Animal Sciences, 2013)
The data on 1 647 Murrah buffaloes from 4 military dairy farms over 34 years was used to investigate the phenoty pic and genetic parameters of early economic traits. The effect of farms and years was significant for all the traits while that between seasons was only significant for first lactation milk yield and milk yield/ day of first calving interval. The phenotypic (0.65 to 0.78) and genetic correlations (0.89Â±0.05 [0 0.98Â±0.05) among first lactation milk yield, milk yield/day of first lactation length and milk yield/day of first calving interval were positive, high and significant.